Vacuum pressure measurement of cold 7Li atoms in the magneto-optical and magnetic trap - Xuejiao Zhang; Rui Li; Jingyi Zhang; Zhehan Li; Haibin Wu (AIP Advances, 2023)
Cold atoms play a very important role in metrology. The ultra-high or extreme-high vacuum pressure can be accurately measured by investigating the collision of cold atoms and residual atoms in the environment. We report a vacuum pressure metrometer using cold 7Li atoms as sensor atoms in a magneto-optical trap and a magnetic trap. The accuracy, uncertainty, and feasibility of the measurements in such two different traps are studied and compared in the pressure range from 10−5 to 10−8 Pa. It is found that the vacuum pressure measurement in a magneto-optical trap is more advantageous with a higher accuracy, higher signal-to-noise ratio, and shorter measurement time under current conditions. The results may be used to realize an applicable cold atom quantum vacuum standard.